HUBUNGAN PENGETAHUAN DAN SIKAP IBU TENTANG PENGELOLAAN DIARE DENGAN KLASIFIKASI DIARE PADA BALITA - Lince Amelia; Mayang Mayang; Almumtahanah almumtahanah; Yenni Lukita (PT. Jurnal Center Indonesia Publisher, 2024)
Background: Diarrhea is the second-leading cause of mortality in children under the age of five. Based on data from the Pontianak City Health Office in 2021, the number of findings was 727 in toddlers. And in 2022, there were as many as 918 findings of diarrhea in toddlers at Gang Sehat Health Center. Mother's factor also affects the occurrence of diarrhea in toddlers. Knowledge is one of the factors causing the high mortality rate due to diarrhea. The importance of maternal knowledge and attitudes in handling diarrheal diseases needs to be discussed because diarrhea that is delayed or improperly handled can cause pain and adverse effects on children, namely infant mortality. Objective: To determine the relationship between mothers' knowledge and attitudes about diarrhea management and the classification of diarrhea in toddlers at the Gang Sehat Health Center. Methods: This study used the accidental sampling method with bivariate analysis using the Chi-Square test. Results: The Chi Square test resulted in a value of 0.934, meaning that the P value > 0.05 indicates that there is no relationship between maternal knowledge and diarrhea classification in toddlers. With the results of the value of 0.443, meaning that the P value > 0.05, there is no relationship between the mother's attitude and diarrhea classification about diarrhea management in toddlers. Conclusion: There is no relationship between knowledge and attitude of mothers with diarrhea classification regarding diarrhea management in toddlers